The Power of Tular Nalar MAFINDO e-Flyer Online Narratives in Shaping Collective Identity - Gani, Rita; Anwar, Citra Rosalyn; Wiguna, King Anugrah; Sarbani, Adven; Satyawati, Niken Pupy (Komunikator, 2026)
Online narratives play a strategic role in shaping collective identity in the digital era. This study examines how Tular Nalar e-flyers produced by MAFINDO, through the integration of local-language taglines, influence identity construction, social solidarity, and collective action. A qualitative approach was employed to analyze 10 e-flyers, representing visual and textual elements, from the final phase of Tular Nalar training (October–December 2024). The analysis focuses on how culturally grounded messages foster emotional connection, enhance audience engagement, and help counter misinformation. The findings indicate that culturally relevant digital narratives not only promote the dissemination of accurate information but also strengthen public participation in social movements. Furthermore, consistent and context-sensitive narratives play a significant role in building trust and social cohesion in digital spaces.